Application of iron-coated zeolites (ICZ) for mine drainage treatment - Jeon, Chil-Sung; Park, Sung-Woo; Baek, Kitae; Yang, Jung-Seok; Park, Joon-Gyu (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2012)
To evaluate iron-coated zeolite (ICZ) for the treatment of mine drainage contaminated arsenic (As), cadmium (Cd) and lead (Pb), a full scale treatment system was installed and operated for nine months. Because it is well known that ICZ can remove As from the water stream, the removal characteristics of cationic metal ions (Cd(II), Cu(II), and Pb(II)) using ICZ were investigated by batch and column experiments before the field test. In the batch test, over 99% of the heavy metal ions were removed by the ICZ within 30 min. The results for the adsorption kinetics and adsorption isotherms were fitted well by a pseudo-second-order model and the Langmuir equation, respectively. An affinity analysis showed that the adsorption of heavy metal ions onto ICZ was favorable. In the column experiments, the cadmium breakthrough point was about 50 bed volumes, while the copper breakthrough occurred immediately in the zeolite column. The lead was not detected in any of the columns in the experiments. In the field experiment, the removal efficiency of arsenic onto ICZ was approximately 99% and the removal of heavy metals onto ICZ field-scale experiments was quite lower compared to the results of laboratory experiments. The value of pH in influent and effluent was about 7.0. Based on the results, ICZ is a suitable material to treat the mine drainage or wastewater bearing As(V) and slightly higher concentration of heavy metals simultaneously.
Keywords: MODIFIED ACTIVATED CARBON; CATIONIC SURFACTANT; SYNTHETIC ZEOLITES; COPPER IONS; TREE FERN; ADSORPTION; REMOVAL; ISOTHERM; SORPTION; MECHANISMS